Universales y sustratos - Pagès, Joan (Análisis Filosófico, 2000)
The general aim of this paper is to defend a theory of properties grounded on universals and the notion of substratum. We offer first a brief survey of sorne problerns concerning the attribution of properties to objects and the sirnilarity of objects. We next characterize the notion of universal by contrasting universals against other entities that have often been postulated in order to account for the mentioned problems. Besides, we distinguish two different theories of properties, both based on the notion of universal: the bundle theory and the substraturn theory, pointing to an unsurrnountable difficulty of the former. In the rest of the paper we try to answer to sorne of the most serious objections that have been posed against the substratum theory. Firstly, we argue that the theory of temporal stages can solve sorne problems deriving from the substantial change and the accidental change; moreover, we give a reply to sorne objections advanced against this theory. Secondly, we offer an elucidation of the notion of substratum as a bare partÍcular. Thirdly, we discuss some objections to the use that the substratum theory makes of these bare particulars as individuators. Our reply is based on a distinction between three different roles that can be ascribed to an entity: a particularizer role and two kinds of individuatory roles (respectively related to transworld and intraworld individuation). We argue that a substratum can perfectly play a rol as a particularizer and also as an intraworld individuator. Finally, we offer a solution to the well known Bradley’s regressum.